Defecatory dysfunction and fecal incontinence in women with or without posterior vaginal wall prolapse as measured by pelvic organ prolapse quantification (POP-Q). (July 2017) - Augusto, Kathiane Lustosa; Bezerra, Leonardo Robson Pinheiro Sobreira; Murad-Regadas, Sthela Maria; Vasconcelos Neto, José Ananias; Vasconcelos, Camila Teixeira Moreira; Karbage, Sara Arcanjo Lino; Bilhar, Andreisa Paiva Monteiro; Regadas, Francisco Sérgio Pinheiro
Abstract: Introduction and hypothesis: Pelvic Floor Dysfunction is a complex condition that may be asymptomatic or may involve a loto f symptoms. This study evaluates defecatory dysfunction, fecal incontinence, and quality of life in relation to presence of posterior vaginal prolapse. Methods: 265 patients were divided into two groups according to posterior POP-Q stage: posterior POP-Q stage ≥2 and posterior POP-Q stage <2. The two groups were compared regarding demographic and clinical data; overall POP-Q stage, percentage of patients with defecatory dysfunction, percentage of patients with fecal incontinence, pelvic floor muscle strength, and quality of life scores. The correlation between severity of the prolapse and severity of constipation was calculated using ρ de Spearman (rho). Results: Women with Bp stage ≥2 were significantly older and had significantly higher BMI, numbers of pregnancies and births, and overall POP-Q stage than women with stage <2. No significant differences between the groups were observed regarding proportion of patients with defecatory dysfunction or incontinence, pelvic floor muscle strength, quality of life (ICIQ-SF), or sexual impact (PISQ-12). POP-Q stage did not correlate with severity of constipation and incontinence. General quality of life perception on the SF-36 was significantly worse in patients with POP-Q stage ≥2 than in those with POP-Q stage <2. Conclusions: The lack of a clinically important association between the presence of posterior vaginal prolapse and symptoms of constipation or anal incontinence leads us to agree with the conclusion that posterior vaginal prolapse probably is not an independent cause defecatory dysfunction or fecal incontinence.